PENGAWASAN/SUPERVISI DALAM LEMBAGA PENDIDIKAN ISLAM DI MTS AL-ANHARIYYAH - Sistri Indriani; Yosi Supenti; Adi Rosadi (CV. ADIBA AISHA AMIRA, 2026)
The Comparing to other states, quality of education in Indonesia including Islamic education has not shown significant progress. It can be verified from the report of PERC, World Bank, and data from UNDP. It is a regret to find the decrease of our education quality. It occurs because supervision of education is done in conventional manner, rigid, and formality limited. Moreover, it may also because instructional activities have not been optimal yet and management of education institution which is less professional. In order to solve the problem, some solutions are offered. One of them is that the implementation of supervision has to be done optimally, procedurally, and professionally. In this case, supervision takes its role as, (1) academic supervision: teacher partner, innovator, and pioneer, instructional and education consultant, teachers counselor, and motivator, (2) managerial supervision: concept drafter, programmer, composer, reporter, and builder. Furthermore, manager (headmaster) has to be able to concentrate and supervise the effort to have a good input through very good process to produce excellent output: moderate input through excellent process produces very good output; and the lower input through a very excellent process resulting better output.